Pengaruh Absensi Pengenalan Wajah Dan Motivasi Kerja Terhadap Disiplin Kerja Karyawan : Studi Kasus Pada PT. XYZ - N.Titi Rahmah; Sugeng Suroso; Ery Teguh Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to determine the effect of the independent variables, namely facial recognition attendance and work motivation, on the dependent variable, namely work discipline. This research was conducted at PT XYZ. The data analysis used was the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 25 application. Data collection was carried out by distributing questionnaires to 46 employees at PT XYZ. Partially, the results show that the facial recognition absentee variable has a significant effect on work discipline, and work motivation has a significant effect on work discipline. Simultaneously the results obtained from this research are that the facial recognition absentee variable and work motivation simultaneously have a significant effect on the work discipline variable.